Modelo matemático para los fenómenos de combustión en un horno de cubilote - Aristizábal Sierra, Ricardo Emilio; Mejía Arango, Héctor Daniel; Silva, Silva; Pineda Arango, Diego Alfonso; Rojas Arango, Juan Marcelo (Revista Facultad de Ingeniería Universidad de Antioquia, 2006)
A mathematical model of the combustion phenomena occurring in a cupola furnace is presented. The most important heterogeneous coke-gas reactions: combustion, CO2 gasification and steam gasification were used for modelling and Matlab (version 5.3) was used to solve said model. Results were compared with experimental data obtained in the cupola furnace of the ecoefficient plant at the University of Antioquia. The model evaluates composition profiles along the furnace column, composition of gases at the chimney and velocity at which metal is fed during this operation. Maximum deviations within 1% for CO2, 5% for CO, 7% for combustion ratio, and 9% for velocity of metal charge were obtained with the model.